2014
DOI: 10.1051/fruits/2014035
|View full text |Cite
|
Sign up to set email alerts
|

WildArbutus unedoL. andRubus ulmifoliusSchott fruits are underutilized sources of valuable bioactive compounds with antioxidant capacity

Abstract: Wild Arbutus unedo L. and Rubus ulmifolius Schott fruits are underutilized sources of valuable bioactive compounds with antioxidant capacity.Abstract -Introduction. Several studies reveal the important role played by 'lesser-known' wild fruits since they contain nutritional and functional compounds which have biological properties. Materials and methods. Our work studied the presence of bioactive compounds such as vitamin C (ascorbic acid and dehydroascorbic acid), total phenolic content, phenolic acids, flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 32 publications
(43 reference statements)
3
20
1
Order By: Relevance
“…Besides ellagic acid derivatives, moderate quantities of caffeic acid derivatives (peak 1 and 2) and non-anthocyanin flavonoid glycosides (peaks 3, 4, 5, 9, 10 and 11) were also found in R. ulmifolius fruit extracts, accounting to 10 and 20%, respectively of the phenolic compounds composition. The phenolic compounds of R. ulmifoius fruits has been previously described by Ruiz-Rodríguez et al (2014) in a sample from Spain, nevertheless, the phenolic profile shown by these authors is completely different from the one obtained herein.…”
Section: Phenolic Composition Of R Ulmifolius Fruitscontrasting
confidence: 90%
See 4 more Smart Citations
“…Besides ellagic acid derivatives, moderate quantities of caffeic acid derivatives (peak 1 and 2) and non-anthocyanin flavonoid glycosides (peaks 3, 4, 5, 9, 10 and 11) were also found in R. ulmifolius fruit extracts, accounting to 10 and 20%, respectively of the phenolic compounds composition. The phenolic compounds of R. ulmifoius fruits has been previously described by Ruiz-Rodríguez et al (2014) in a sample from Spain, nevertheless, the phenolic profile shown by these authors is completely different from the one obtained herein.…”
Section: Phenolic Composition Of R Ulmifolius Fruitscontrasting
confidence: 90%
“…Several studies have been performed using different Rubus species, such as Rubus ideaus, Rubus takesimensis and Rubus suavissimis (Milivojevic et al, 2011;Uhler & Yang, 2018;Yang, Pak, & Kim, 2018). Deeper studies were carried out in blackberry (Van de Velde, Pirovani, & Drago, 2018), in Rubus ulmifolium flowers buds and open flowers (Barros et al, 2010), and in Rubus ulmifolium fruits (Ruiz-Rodríguez et al, 2014). The present study evidences novelty in the chemical and bioactive characterization of R. ulmifolium fruits, and deepens the evaluation of compounds with bioactive interest, such as polyphenols.…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations